Tissue invasion and alteration in eggplant infected with Verticillium dahliae: A light and transmission electron microscopy study - Ouellette, Guillemond; Chamberland, Hélène (Phytoprotection, 2006)
AbstractLight and transmission electron microscopy observations of Verticillium-inoculated eggplants are reported. Results of tests for cellulose and chitin are also presented. Opaque, vessel wall lining matter (VWLM) generally occurred, connected to elements identified as fungal cells, and extending into vessel secondary walls and across pits. VWLM was also confluent with similar matter extensively pervading middle lamellae and causing their alterations. The thickest VWLM was stratified as alternating opaque and more lucent bands, with the opaque ones being similar to the first layer deposited. Many loops were included in or bulged from the VWLM layers. Lace-like structures also occurred in vessel lumina as apparent distensions of the basic, first opaque layer of this VWLM. Large amounts of similar opaque matter occurred in the periphery of paratracheal cells with altered content. This matter contained filamentous-like structures and frequently opaque particles reminiscent of ribosomes. The pitted areas were much altered as an internal shred-like network, unlabelled for cellulose, covered by an outer opaque and compact cellulose-labelled layer, itself overlaid by an unlabelled VWLM. Release of labelled material from these altered areas only occurred at locations of VWLM ruptures. Detachment and alterations of the adjacent vessel wall secondary thickenings were noticeable and accounted for the presence of lucent cellulose-labelled matter in vessel lumina.